Systematic review and meta-analysis: The association between emotional intelligence and subjective well-being in adolescents - Llamas-Díaz, Desirée; Cabello-González, Rosario; Megías-Robles, Alberto; Fernández-Berrocal, Pablo (Wiley, 2022)
Introduction Emotional intelligence (EI) is a psychological protective factor that can improve subjective well-being (WB) in adolescents. This study aims to establish the overall relationship between different EI models (performance-based ability model, self-report ability model, and self-report mixed model) and subjective WB in adolescents, analyze the affective WB and cognitive WB components, and examine the moderating effect of EI models on both types of subjective WB. Method We searched PsycINFO and WOS databases. Eligible studies reported an association between EI and subjective WB in adolescents aged 10–19 years using instruments that directly measure subjective WB. In addition, two meta-analyses were conducted, one for the relationship between EI and affective WB and the other for EI and cognitive WB. Results A total of 41 studies were included, of which 37 were pooled in the meta-analyses. We found a significant positive relationship between EI and affective WB (estimated effect size = 0.35) and between EI and cognitive WB (estimated effect size = 0.27). Regarding EI models, self-report ability showed an estimated effect size of 0.33 for affective WB and 0.27 for cognitive WB. For the self-report mixed model, we obtained an estimated effect size of 0.42 for affective WB and 0.37 for cognitive WB. Conclusions Establishing a quantitative relationship between EI and subjective WB makes it possible to implement clinical and educational prevention measures. Introducing EI training in educational and clinical settings can increase subjective WB, significantly impacting the prevention of emotional disorders in adolescents.
Keywords: Adolescentes -- Psicología; Adolescents; Emotional intelligence; Meta‐analysis; Subjective well‐being; Systematic review